Analisis Pemilihan Moda Kereta Api Ekonomi AC dan Bus Ekonomi AC Jurusan Yogyakarta – Madiun - PURNOMO, HERIBERTUS KURNIA EKO ([Yogyakarta] : Universitas Gadjah Mada, 2015)
People mobility between Madiun and Yogyakarta is increasing due to the increasing of workers, social relations, education, trading activity between the two cities and offcourse because of the tourism destination. Public transport between major cities such as bus or train is necessary to make time and cost more efficient and to support economic growth and people mobility. Nowadays public transport such as buses is widely available, while for rail transport is still not. This study was conducted to examine the characteristics and analyze the possibility to increase the probability of selecting the railway mode by identifying factors that influence the mode choice. Stated preference methods used to analize the utility variance between air conditioned economic train and air conditioned economic bus, so we know the mode models choice of both these modes. Modal choice probability is measured by the binomial logit function. The research results showed that the air conditioned economic train and air conditioned economic bus has a different market share. By the time the difference between the fares of air conditioned economic train and air conditioned economic bus is IDR-11.300 bus passengers are started thinking to use air conditioned economic train. And if it decrease again, while other attributes remain the same, passengers who chose the air conditioned economic train will be greater than the air conditioned economic bus. At the time of the travel time difference between air conditioned economic train and air conditioned economic bus -170 minutes, bus passengers are started thinking to use air conditioned economic train. The waiting time and comfortable has no effect on modal choice between Yogyakarta to Madiun air conditioned economic train and air conditioned economic bus. Keywords: modal choice models, stated preference, probability